E-training adoption in Nigeria civil service: Role of power supply, perceived ease of use and perceived usefulness - Zainab, Bello; Pangil, Faizuniah; Bhatti, Muhammad Awais (CRC Press, 2015)
The Nigerian civil service is still using conventional method to train it work force.The review of literature shows the state of power supply in the country this paper intends to explain the role power supply in the adoption of electronic training in the Nigerian civil service.This conceptual paper proposed of use in Technology Acceptance Model (TAM) mediates power supply and e-training adoption.This paper explains the relationship of power supply and perceived ease of use.Secondary source of data was used in acquiring information for this conceptual write up.This paper will enable policy makers comprehend the usefulness of e-training in the civil service and also give way for more research in training and development at the work place.This paper suggest power supply as an external variable to Technology Acceptance Model (TAM) as contribution to existing literature on e-training.